Latex mask and preparation method
By combining waterborne polyurethane emulsion modified with nano-hydroxyapatite and vinyltrimethoxysilane with natural latex, a latex mask with good breathability, high flexibility, and excellent durability was prepared. This solved the problems of insufficient breathability, flexibility, and durability of existing latex masks, and improved wearing comfort and service life.
Patent Information
- Application Number
- CN202411357482.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-27
- Publication Date
- 2025-01-10
AI Technical Summary
Existing latex masks are inadequate in terms of breathability, flexibility, and durability, resulting in insufficient comfort and lifespan.
Waterborne polyurethane was modified with nano-hydroxyapatite and vinyltrimethoxysilane, and zeolite powder was added to form a composite modified waterborne polyurethane emulsion. This emulsion was then mixed with natural latex, defoamer, thickener, and wetting agent, and latex masks were prepared through impregnation and drying processes.
It significantly improves the breathability and flexibility of latex masks, enhances durability, and increases wearing comfort and lifespan.
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of natural rubber compositions, in particular to a latex mask and a preparation method thereof. Background Art
[0002] Latex masks are props used for performances, masquerade balls, role-playing or special occasions. Masks of various shapes and expressions can be made to suit different roles and needs. Latex masks are usually made of different types of latex, mainly including natural latex, synthetic latex and artificial latex. Natural latex comes from the latex of rubber trees. It has excellent elasticity, softness, breathability, etc., which helps to reduce the stuffiness when worn and provides good comfort and fit; but it is somewhat allergic. The specific proteins contained in natural latex may cause allergic symptoms and are not suitable for all people. Waterborne polyurethane is an environmentally friendly polymer material with excellent hypoallergenicity, wear resistance and tear resistance. It provides good durability. Its softness, breathability and elasticity in latex mask applications are lower than natural latex.
[0003] Latex masks need to have good flexibility and elasticity, and can quickly return to their original shape after stretching, so that they can be worn by different face shapes; they also need to have good durability and be able to withstand a certain degree of pulling and frequency of use; wearing a mask for a long time may cause discomfort, and a mask with strong comfort can reduce the discomfort of the wearer. In terms of improving comfort, the weight of the latex mask can be reduced to avoid the sense of oppression or fatigue caused by long-term wearing; the formula can also be adjusted to select a softer latex material to make the mask fit the facial contour more closely and reduce discomfort; low-sensitivity latex materials can be selected to reduce irritation to sensitive skin; improve the breathability of the latex mask, allow air circulation, and reduce the feeling of stuffiness when wearing. The prop latex mask needs to have high flexibility, durability and comfort, so that it is suitable for different face shapes in actual use and has a long service life, while ensuring the comfort of long-term wearing, thereby improving the overall user experience and meeting the needs of different occasions.
[0004] CN113549243A discloses a cool breathable latex product and a preparation method thereof. The invention adopts a roller coating method to apply a coating glue containing phase change microcapsules to the surface layer of the latex product and the pore structure below the surface layer. Since the paraffin and other substances in the phase change microcapsules absorb heat to keep the temperature constant, the human body is brought to a contact cool feeling. The coating technology will not form a dense film on the latex surface, avoiding the inconvenience caused by the dense film formed by the existing gel process to the human body heat dissipation and sweat evaporation. The technology does not destroy the original latex structure, does not block the pores of the latex surface, retains its breathable characteristics, and allows users to feel cool and breathable. The higher the content of the phase change microcapsules, the higher the sizing amount, and the better the cooling effect of the breathable cool latex product made.
[0005] CN115593060A discloses a natural antibacterial and antimicrobial breathable fabric and a preparation method thereof. The invention makes the fabric waterproof and breathable while having a certain elasticity through the arrangement of a tetrafluoroethylene waterproof and breathable membrane layer, a breathable strip and a connecting protrusion, and the stable structure makes the fabric more firm and strong. A number of breathable through holes are evenly opened on the surface of the polyurethane anti-wrinkle layer, and the breathable through holes are connected to the gap between the filling cavity and the breathable strip, which greatly enhances the breathability of the fabric and improves the efficiency of moisture absorption and perspiration. The method of mixing silver fibers and antibacterial particles reduces the cost of preparing antibacterial and breathable fabrics, while also avoiding direct contact between the antibacterial particles and human skin, and at the same time has excellent broad-spectrum antibacterial ability.
[0006] The solutions reported in the above patent documents all solve the problem of air permeability, but do not solve the problem of improving flexibility and durability at the same time. In actual use, low flexibility will reduce comfort, and poor durability will make it unsuitable for long-term use and have a high scrap rate. Therefore, it is urgent to provide a latex mask product with good air permeability, high flexibility and good durability. Summary of the invention
[0007] In view of the above-mentioned defects of the prior art, the technical problem to be solved by the present invention is to improve the air permeability, flexibility, durability and comfort of latex mask materials.
[0008] To achieve the above object, the present invention provides a latex mask and a preparation method thereof.
[0009] The preparation method of the latex mask comprises the following steps, measured in parts by weight: (1) Add 10-15 parts of 1,5-pentanediol and 0.5-1 parts of sodium 5-sulfoisophthalate to 250-350 parts of water, stir at 160-180°C for 1-2 hours, cool to 70-90°C, add 0.05-0.15 parts of dibutyltin dilaurate and 10-15 parts of glutaric acid, stir at 130-150°C for 1-2 hours, concentrate and dry to obtain sulfonate diol; (2) 8-10 parts of isophorone diisocyanate, 8-10 parts of polytetramethylene glycol, and 0.1-0.2 parts of trimethylolpropane are mixed, and 0.5-1.5 parts of emulsifier, 0.1-0.2 parts of nano-hydroxyapatite, and 0.4-0.6 parts of silane modifier are added, and ultrasonic dispersion is performed for 10-30 minutes to obtain a waterborne polyurethane prepolymer; 0.02-0.08 parts of catalyst and 2-3 parts of sulfonate diol are added, and the mixture is stirred at 70-80°C for 3-5 hours, and then the temperature is lowered to 60-70°C and 10-20 parts of Acetone is added to reduce the viscosity, 0.5-1 parts of chain extender and 0.2-0.4 parts of 1,4-butanediol are added, stirring is continued for 1-2 hours, cooled to 30-40°C, 0.2-0.6 parts of triethylamine are added for neutralization reaction and stirring is continued for 0.5-1 hour, added to 40-50 parts of water and stirred at a speed of 1000-1500r / min for 0.5-1 hour, and finally 0.1-0.3 parts of ethylenediamine are added and stirred at room temperature for 1-1.5 hours for further chain extension, and acetone is removed by concentration at 50°C to obtain the modified waterborne polyurethane emulsion; (3) adding 20-30 parts of zeolite powder to 140-200 parts of water, and ultrasonically dispersing for 10-30 minutes to obtain a zeolite powder dispersion, adding the modified aqueous polyurethane emulsion obtained in step (2) to the zeolite powder dispersion, and stirring at room temperature for 1-1.5 hours to obtain a composite modified aqueous polyurethane emulsion; (4) 30-40 parts of natural latex, 50-60 parts of modified waterborne polyurethane emulsion, 0.5-1 part of defoaming agent, 0.5-1 part of thickener and 0.4-0.6 part of wetting agent are mixed, and mixed in a high-speed disperser at 1500-2000 r / min for 0.5-1 hour to obtain a mixed emulsion, and the mask mold is directly immersed in the mixed emulsion for 2-4 times, dried at 80-100° C., and demolded after molding to obtain the latex mask.
[0010] In the step (2), the particle size of the nano-hydroxyapatite is 100-300 nm.
[0011] The silane modifier in step (2) is vinyltrimethoxysilane.
[0012] The emulsifier in step (2) is dodecylphenol polyoxyethylene ether OP-10.
[0013] The catalyst in step (2) is dibutyltin dilaurate.
[0014] In the step (2), the chain extender is any one of 2,2-dihydroxymethylpropionic acid, 1,2-propylene glycol, diethylene glycol, 2-methylpentanediamine, and 1,6-hexanediamine.
[0015] The thickener in step (4) is hydroxyethyl cellulose.
[0016] The immersion thickness in the step (4) is 0.2-0.4 cm.
[0017] The latex mask and preparation method of the present invention are intended to prepare a latex mask material with improved air permeability, flexibility, durability and comfort. Isophorone diisocyanate is used as a precursor of a hard segment, reacts with polytetrahydrofuran diol and trimethylolpropane of a soft segment to form a basic skeleton of polyurethane, nano-hydroxyapatite and vinyl trimethoxysilane are added to the monomer for modification, dodecylphenol polyoxyethylene ether OP-10 emulsifier is promoted for mixing, acetone is added for viscosity adjustment, chain extender increases the length and flexibility of the molecular chain, triethylamine is used for neutralization reaction, ethylenediamine (EDA) is further chain extended to increase the crosslinking density, and a modified waterborne polyurethane emulsion is obtained, and zeolite powder is further added for compounding to obtain a composite modified waterborne polyurethane emulsion. Finally, the composite modified waterborne polyurethane emulsion, natural latex, defoamer, thickener and wetting agent are mixed, stirred evenly by high dispersion, and the latex mask of the present invention is obtained by impregnation and drying process.
[0018] Zeolite powder has a loose, porous structure. When people wear a latex mask to breathe, the CO2 produced in the body will accumulate and cause discomfort if it is not quickly discharged. The adsorption of the porous structure of zeolite powder can adsorb CO2 polar molecules, and the adsorption effect on smaller molecules such as O2 is weaker. It can quickly realize the dynamic exchange of gas molecules inside and outside the mask, which not only accelerates the discharge of internal moisture and CO2, but also helps the entry of fresh air from the outside, significantly improving the breathability and comfort of the latex mask. In order to improve the interfacial interaction between organic and inorganic substances in the polymer of zeolite powder, sulfonic acid groups were introduced into modified waterborne polyurethane through sulfonate diol, which not only promoted the transport of CO2 under elevated relative humidity, but also improved the interfacial interaction between the two phases through hydrogen bonds.
[0019] The addition of nano-hydroxyapatite enhances the biocompatibility of latex materials. Its high specific surface area and unique nanostructure enhance interfacial bonding, effectively disperse stress, reduce the friction coefficient of the material, improve the tensile resistance and wear resistance of the material, and thus enhance durability; high specific surface area and surface energy promote the formation of an ordered nanostructure in the polymer matrix, increase the porosity of the material, and thus improve the air permeability and flexibility. The introduction of vinyl trimethoxysilane forms chemical crosslinks with polyurethane prepolymers, enhancing the cohesion and tensile resistance of the material; it also helps to improve the wear resistance of the material, reduce damage caused by friction, increase the surface smoothness of the latex mask, not only enhance flexibility and wear resistance, but also improve air permeability through its low surface energy characteristics; flexible siloxane segments improve the flexibility of the material, making the mask more comfortable to wear and adapting to different facial contours. The improvement in durability allows the latex mask to maintain good performance under repeated use, reducing damage and scrapping, and increasing the number of uses and life.
[0020] Beneficial effects of the present invention: Compared with the prior art, the latex mask of the present invention improves the material permeability, flexibility, durability and comfort, introduces nano-hydroxyapatite and vinyl trimethoxysilane to modify the waterborne polyurethane monomer, further adds zeolite powder for compounding, and then mixes with natural latex, defoamer, thickener and wetting agent, disperses and dries to obtain the latex mask of the present invention. The improvement of flexibility makes the latex mask suitable for wearing on different face shapes, making the latex mask softer and more comfortable; the improvement of air permeability makes it more breathable during use, allowing air circulation, and reducing discomfort such as stuffiness when wearing; the addition of zeolite powder enables people to quickly realize the dynamic exchange of gas molecules inside and outside the mask when wearing the latex mask for breathing, which not only accelerates the discharge of internal moisture and CO2, but also helps the entry of external fresh air, significantly improving the air permeability and comfort of the latex mask. The enhancement of tensile strength and breaking growth rate improves the durability in practical applications. The improvement in durability enables the latex mask to maintain good performance after repeated use, reduces damage and scrapping, increases the number of uses and lifespan, and meets the market demand for high-performance latex masks. DETAILED DESCRIPTION
[0021] The parameters of the specific chemical substances used in the examples are from the following sources: Natural latex: Natural latex: brand is Sankeshu, model is THR LATEX, solid content is 60wt%, pH value is 8±1.
[0022] Nano-hydroxyapatite: particle size is 200nm, the manufacturer is Jinan Shenghe Chemical Co., Ltd., and the product number is HH3190J71D4A.
[0023] Zeolite powder: 400 mesh, bulk density 0.45 g / mL, manufacturer is Zhengzhou Chaorong Nanomaterials Co., Ltd., model is 4A.
[0024] Wetting agent OT-75: content is 75wt%, brand is Shihaihua, model is OT-75.
[0025] Defoaming agent DF 675: content is 98wt%, brand is Haimingsdeqian, model is DF 675.
[0026] Dodecylphenol polyoxyethylene ether OP-10: CAS number is 9041-29-6, Xingtai Xinlanxing Technology Co., Ltd., model is 12D-4, hydroxyl value is 120±6, and HLB value is 8.5-9.4.
[0027] Hydroxyethyl cellulose: CAS number is 9004-62-0.
[0028] Isophorone diisocyanate: CAS number is 4098-71-9.
[0029] Polytetrahydrofurandiol: CAS number is 25190-06-1, the manufacturer is Hubei Xinkang Pharmaceutical Chemical Co., Ltd., and the product number is XK0844.
[0030] Trimethylolpropane: CAS number is 77-99-6.
[0031] Dibutyltin dilaurate: CAS number is 77-58-7.
[0032] 2,2-Dihydroxymethylpropionic acid: CAS number is 4767-03-7.
[0033] Vinyltrimethoxysilane: CAS number is 2768-02-7.
[0034] γ-Aminopropyltriethoxysilane: CAS number is 919-30-2.
[0035] N-(β-aminoethyl)-γ-aminopropylmethyldimethoxysilane: CAS number is 3069-29-2.
[0036] 1,5-Pentanediol: CAS number is 111-29-5.
[0037] Glutaric acid: CAS number is 110-94-1.
[0038] Sodium 5-sulfoisophthalate: CAS number is 6362-79-4.
[0039] Example 1 A method for preparing a latex mask comprises the following steps: (1) Add 14 g of 1,5-pentanediol and 0.8 g of sodium 5-sulfoisophthalate to 300 g of water, stir at 180° C. for 1 hour, cool to 80° C., add 0.1 g of dibutyltin dilaurate and 14 g of glutaric acid, stir at 140° C. for 1 hour, and concentrate to dryness to obtain sulfonate diol; (2) 90 g of isophorone diisocyanate, 100 g of polytetramethylene glycol, and 2 g of trimethylolpropane were mixed, and 12 g of dodecylphenol polyoxyethylene ether OP-10, 2 g of nano-hydroxyapatite, and 5 g of vinyl trimethoxysilane were added, and ultrasonic dispersion was performed at 25 kHz for 20 minutes to obtain a waterborne polyurethane prepolymer; 0.6 g of dibutyltin dilaurate and 25 g of sulfonate diol were added, and the mixture was stirred at 75° C. for 4 hours, and the mixture was cooled to 65° C. and 150 g of acetone was added to reduce the viscosity, and 8 g of 2,2-dimethylolpropionic acid and 3 g of 1,4-butanediol were added, and the mixture was stirred for 1 hour, and the mixture was cooled to 35° C. and 5 g of triethylamine was added to neutralize the mixture and stirred for 0.5 hour, and the mixture was added to 450 g of water and stirred at a speed of 1300 r / min for 0.5 hour, and finally 2 g of ethylenediamine was added and stirred at room temperature for 1 hour to further extend the chain, and the mixture was concentrated at 50° C. to remove acetone, and the modified waterborne polyurethane emulsion was obtained; (3) adding 25 g of zeolite powder to 150 g of water, and dispersing the mixture by ultrasonic at 25 kHz for 20 minutes to obtain a zeolite powder dispersion, adding the modified aqueous polyurethane emulsion obtained in step (2) to the zeolite powder dispersion, and stirring at room temperature for 1 hour to obtain a composite modified aqueous polyurethane emulsion; (4) 350 g of natural latex, 550 g of composite modified waterborne polyurethane emulsion, 7 g of defoamer DF 675, 7 g of hydroxyethyl cellulose, and 5 g of wetting agent OT-75 were mixed, and mixed in a high-speed disperser at 1600 r / min for 0.5 h to obtain a mixed emulsion. The mask mold was directly immersed in the mixed emulsion with an immersion thickness of 0.2 cm, and was immersed three times. The mold was dried at 90° C. and demolded after molding to obtain the latex mask.
[0040] Example 2 A method for preparing a latex mask comprises the following steps: (1) 90 g of isophorone diisocyanate, 100 g of polytetramethylene glycol, and 2 g of trimethylolpropane were mixed, and 12 g of dodecylphenol polyoxyethylene ether OP-10, 2 g of nano-hydroxyapatite, and 5 g of vinyl trimethoxysilane were added, and ultrasonic dispersion was performed at 25 kHz for 20 minutes to obtain a waterborne polyurethane prepolymer; 0.6 g of dibutyltin dilaurate was added, and the mixture was stirred at 75° C. for 4 hours, and the mixture was cooled to 65° C. and 150 g of acetone was added to reduce the viscosity, and 8 g of 2,2-dimethylolpropionic acid and 3 g of 1,4-butanediol were added, and the mixture was stirred for 1 hour, and the mixture was cooled to 35° C. and 5 g of triethylamine was added to neutralize the mixture and stirred for 0.5 hour, and the mixture was added to 450 g of water and stirred at a speed of 1300 r / min for 0.5 hour, and finally 2 g of ethylenediamine was added and stirred at room temperature for 1 hour to further extend the chain, and the mixture was concentrated at 50° C. to remove acetone, and the modified waterborne polyurethane emulsion was obtained; (2) 350 g of natural latex, 550 g of modified waterborne polyurethane emulsion, 7 g of defoamer DF 675, 7 g of hydroxyethyl cellulose, and 5 g of wetting agent OT-75 were mixed, and mixed in a high-speed disperser at 1600 r / min for 0.5 h to obtain a mixed emulsion. The mask mold was directly immersed in the mixed emulsion with an immersion thickness of 0.2 cm, and was immersed three times. The mold was dried at 90° C. and demolded after molding to obtain the latex mask.
[0041] Example 3 A method for preparing a latex mask comprises the following steps: (1) 90 g of isophorone diisocyanate, 100 g of polytetramethylene glycol, and 2 g of trimethylolpropane were mixed, 12 g of dodecylphenol polyoxyethylene ether OP-10 and 7 g of nano-hydroxyapatite were added, and ultrasonic dispersion was performed at 25 kHz for 20 minutes to obtain a waterborne polyurethane prepolymer; 0.6 g of dibutyltin dilaurate was added, and the mixture was stirred at 75° C. for 4 hours, and the mixture was cooled to 65° C. and 150 g of acetone was added to reduce the viscosity, and 8 g of 2,2-dihydroxymethylpropionic acid and 3 g of 1,4-butanediol were added and stirred for 1 hour, and the mixture was cooled to 35° C. and 5 g of triethylamine was added for neutralization and stirred for 0.5 hour, and the mixture was added to 450 g of water and stirred at a speed of 1300 r / min for 0.5 hour, and finally 2 g of ethylenediamine was added and stirred at room temperature for 1 hour to further extend the chain, and the mixture was concentrated at 50° C. to remove acetone, and the modified waterborne polyurethane emulsion was obtained; (2) 350 g of natural latex, 550 g of modified waterborne polyurethane emulsion, 7 g of defoamer DF 675, 7 g of hydroxyethyl cellulose, and 5 g of wetting agent OT-75 were mixed, and mixed in a high-speed disperser at 1600 r / min for 0.5 h to obtain a mixed emulsion. The mask mold was directly immersed in the mixed emulsion with an immersion thickness of 0.2 cm, and was immersed three times. The mold was dried at 90° C. and demolded after molding to obtain the latex mask.
[0042] Example 4 A method for preparing a latex mask comprises the following steps: (1) 90 g of isophorone diisocyanate, 100 g of polytetramethylene glycol, and 2 g of trimethylolpropane were mixed, 12 g of dodecylphenol polyoxyethylene ether OP-10 and 7 g of vinyl trimethoxysilane were added, and ultrasonic dispersion was performed at 25 kHz for 20 minutes to obtain a waterborne polyurethane prepolymer; 0.6 g of dibutyltin dilaurate was added, and the mixture was stirred at 75° C. for 4 hours, and the mixture was cooled to 65° C. and 150 g of acetone was added to reduce the viscosity, and 8 g of 2,2-dimethylolpropionic acid and 3 g of 1,4-butanediol were added, and the mixture was stirred for 1 hour, and the mixture was cooled to 35° C. and 5 g of triethylamine was added to neutralize the mixture and stirred for 0.5 hour, and the mixture was added to 450 g of water and stirred at a speed of 1300 r / min for 0.5 hour, and finally 2 g of ethylenediamine was added and stirred at room temperature for 1 hour to further extend the chain, and the mixture was concentrated at 50° C. to remove acetone, and the modified waterborne polyurethane emulsion was obtained; (2) 350 g of natural latex, 550 g of modified waterborne polyurethane emulsion, 7 g of defoamer DF 675, 7 g of hydroxyethyl cellulose, and 5 g of wetting agent OT-75 were mixed, and mixed in a high-speed disperser at 1600 r / min for 0.5 h to obtain a mixed emulsion. The mask mold was directly immersed in the mixed emulsion with an immersion thickness of 0.2 cm, and was immersed three times. The mold was dried at 90° C. and demolded after molding to obtain the latex mask.
[0043] Comparative Example 1 A method for preparing a latex mask comprises the following steps: (1) 90g of isophorone diisocyanate, 100g of polytetramethylene glycol, and 2g of trimethylolpropane are mixed, 12g of dodecylphenol polyoxyethylene ether OP-10, 2g of nano-hydroxyapatite, and 5g of γ-aminopropyltriethoxysilane are added, and ultrasonic dispersion is performed at 25kHz for 20 minutes to obtain a waterborne polyurethane prepolymer; 0.6g of dibutyltin dilaurate is added, and the mixture is stirred at 75°C for 4 hours, and the mixture is cooled to 65°C and 150g of acetone is added to reduce the viscosity, and 8g of 2,2-dimethylolpropionic acid and 3g of 1,4-butanediol are added and stirred for 1 hour, and the mixture is cooled to 35°C and 5g of triethylamine is added for neutralization and stirring for 0.5 hour, and the mixture is added to 450g of water and stirred at a speed of 1300r / min for 0.5 hour, and finally 2g of ethylenediamine is added and stirred at room temperature for 1 hour to further extend the chain, and the mixture is concentrated at 50°C to remove acetone to obtain the modified waterborne polyurethane emulsion; (2) 350 g of natural latex, 550 g of modified waterborne polyurethane emulsion, 7 g of defoamer DF 675, 7 g of hydroxyethyl cellulose, and 5 g of wetting agent OT-75 were mixed, and mixed in a high-speed disperser at 1600 r / min for 0.5 h to obtain a mixed emulsion. The mask mold was directly immersed in the mixed emulsion with an immersion thickness of 0.2 cm, and was immersed three times. The mold was dried at 90° C. and demolded after molding to obtain the latex mask.
[0044] Comparative Example 2 A method for preparing a latex mask comprises the following steps: (1) 90 g of isophorone diisocyanate, 100 g of polytetramethylene glycol, and 2 g of trimethylolpropane were mixed, and 12 g of dodecylphenol polyoxyethylene ether OP-10, 2 g of nano-hydroxyapatite, and 5 g of N-(β-aminoethyl)-γ-aminopropylmethyldimethoxysilane were added, and ultrasonic dispersion was performed at 25 kHz for 20 minutes to obtain a waterborne polyurethane prepolymer; 0.6 g of dibutyltin dilaurate was added, and the mixture was stirred at 75° C. for 4 hours, and the mixture was cooled to 65° C. and 150 g of acetone was added to reduce the viscosity, and 8 g of 2,2-dimethylolpropionic acid and 3 g of 1,4-butanediol were added, and the mixture was stirred for 1 hour, and the mixture was cooled to 35° C. and 5 g of triethylamine was added to neutralize the mixture and stirred for 0.5 hour, and the mixture was added to 450 g of water and stirred at a speed of 1300 r / min for 0.5 hour, and finally 2 g of ethylenediamine was added and stirred at room temperature for 1 hour to further extend the chain, and the mixture was concentrated at 50° C. to remove acetone, and the modified waterborne polyurethane emulsion was obtained; (2) 350 g of natural latex, 550 g of modified waterborne polyurethane emulsion, 7 g of defoamer DF 675, 7 g of hydroxyethyl cellulose, and 5 g of wetting agent OT-75 were mixed, and mixed in a high-speed disperser at 1600 r / min for 0.5 h to obtain a mixed emulsion. The mask mold was directly immersed in the mixed emulsion with an immersion thickness of 0.2 cm, and was immersed three times. The mold was dried at 90° C. and demolded after molding to obtain the latex mask.
[0045] Comparative Example 3 A method for preparing a latex mask comprises the following steps: (1) 90 g of isophorone diisocyanate, 100 g of polytetramethylene glycol, and 2 g of trimethylolpropane were mixed, and ultrasonic dispersion was performed at 25 kHz for 20 minutes to obtain a waterborne polyurethane prepolymer; 0.6 g of dibutyltin dilaurate was added, and the mixture was stirred at 75° C. for 4 hours, and the temperature was lowered to 65° C. and 150 g of acetone was added to reduce the viscosity, and 8 g of 2,2-dimethylolpropionic acid and 3 g of 1,4-butanediol were added, and the mixture was stirred for 1 hour, and the mixture was cooled to 35° C. and 5 g of triethylamine was added for neutralization reaction and stirred for 0.5 hour, and the mixture was added to 450 g of water and stirred at 1300 r / min for 0.5 hour, and finally 2 g of ethylenediamine was added and stirred at room temperature for 1 hour to further extend the chain, and the mixture was concentrated at 50° C. to remove acetone, and the waterborne polyurethane emulsion was obtained; (2) 350 g of natural latex, 550 g of aqueous polyurethane emulsion, 7 g of defoamer DF 675, 7 g of hydroxyethyl cellulose, and 5 g of wetting agent OT-75 were mixed, and mixed in a high-speed disperser at 1600 r / min for 0.5 h to obtain a mixed emulsion. The mask mold was directly immersed in the mixed emulsion with an immersion thickness of 0.2 cm, and was immersed three times. The mold was dried at 90° C. and demolded after molding to obtain the latex mask.
[0046] Comparative Example 4 A method for preparing a latex mask comprises the following steps: 900 g of natural latex, 7 g of defoamer DF 675, 7 g of hydroxyethyl cellulose and 5 g of wetting agent OT-75 were mixed, and mixed at a high speed disperser at 1600 r / min for 0.5 hour to obtain a mixed emulsion. The mask mold was directly immersed in the mixed emulsion with an immersion thickness of 0.2 cm, and was immersed 3 times. The mixture was dried at 90° C. and demolded after molding to obtain the latex mask.
[0047] Test Example 1 Air permeability test The latex masks prepared in Examples 1-4 and Comparative Examples 1-4 were cut into 3 flat samples with a length and width of 200 mm and a thickness of 6 mm, and the air permeability tester was used to test the air permeability. The higher the air permeability, the higher the air permeability. The test data were averaged and summarized as shown in Table 1. The air permeability tester manufacturer is Zhejiang Sanjiang Instrument Co., Ltd., model is YG461H, the test sample thickness range is 0-12 mm, and the power is 1500W. .
[0048] It can be seen from the above table that Comparative Example 4 uses natural latex as the main raw material, and the natural latex material itself has extremely high air permeability, while the latex mask of Example 2 is modified by modifying the water-based polyurethane with nano-hydroxyapatite and vinyltrimethoxysilane, and then compounded with natural latex for use as the main raw material; Example 1 adds zeolite powder to Example 2 for compounding. The addition of zeolite powder helps to increase the porosity of the material due to its porous structure characteristics, further enhancing the air permeability, and can effectively improve the permeability of carbon dioxide. When breathing while wearing the mask in actual application, the CO2 produced by metabolism in the body needs to be effectively discharged, which reduces the CO2 concentration inside the mask, helps to maintain the air quality inside the mask, and reduces the stuffiness and discomfort felt by the user, thereby improving the air permeability and comfort of the mask. The air permeability of Examples 1-2 is closest to that of Comparative Example 4, in which vinyl trimethoxysilane improves the microstructure of the material. It is judged that the vinyl functional group reacts with the amino functional group in the polyurethane to form a stable three-dimensional network structure, which adds more air permeable channels, and the poor air permeability of the modified polyurethane is solved. Then, nano inorganic particles are introduced; nano hydroxyapatite improves the dispersibility of the polymer matrix, increases the porosity, forms microscopic pores, and improves the air permeability of the latex mask without sacrificing the strength and durability of the mask. In Example 3, only nano hydroxyapatite is added to participate in the modification of waterborne polyurethane. The nano particles increase the porosity of the material and also improve the air permeability. In Example 4, only vinyl trimethoxysilane is used to modify the waterborne polyurethane. In Comparative Example 3, natural latex and waterborne polyurethane are simply added for simple mixing. Compared with Comparative Example 3, the air permeability of Example 4 is still improved to a certain extent, indicating that vinyl trimethoxysilane plays a certain positive role in improving the air permeability. Compared with Example 2, Comparative Examples 1 and 2 replace vinyltrimethoxysilane with γ-aminopropyltriethoxysilane and N-(β-aminoethyl)-γ-aminopropylmethyldimethoxysilane. The degree of optimization of the pore structure is not as good as that of Example 2, so the air permeability is slightly lower than that of Example 2.
[0049] Test Example 2 Flexibility test According to the preparation methods of Examples 1-4 and Comparative Examples 1-3, three smooth, flat latex mask samples with a size of 200mm×200mm×6mm were prepared respectively. Since its physical properties have commonalities with the surface properties of the paint film, the latex mask sample was used as the test substrate in Test Example 2, and the sample surface was regarded as a paint film to simulate the flexibility of the paint film in actual application. The test was based on the national standard GB / T 1731-2020 "Determination of Flexibility of Paint Film and Putty Film", and the thickness of the shaft rod of the paint film flexibility tester was 1mm, 2mm, and 3mm respectively; the test results were expressed as follows: the minimum shaft rod diameter (mm) at which no reticulation, cracks, or peeling was observed in at least two tests; the test data was averaged and summarized as shown in Table 2. .
[0050] In Test Example 2, the flexibility test was conducted on Examples 1-4 and Comparative Examples 1-3. The latex mask of Comparative Example 4 is made of natural latex, which is very flexible and does not require testing. The differences in the data in the flexibility test are mainly attributed to the specific chemical properties of vinyl trimethoxysilane and its distribution in the material. The difference between the latex masks of Examples 1-4 is that Example 2 adds nano hydroxyapatite and vinyl trimethoxy silane to modify the waterborne polyurethane, and Example 1 adds zeolite powder to the modified waterborne polyurethane on the basis of Example 2 for loading. Example 3 adds nano hydroxyapatite to modify the waterborne polyurethane, and Example 4 adds vinyl trimethoxy silane to modify the waterborne polyurethane. By comparison, it is found that Examples 1-4 can maintain good flexibility under 1mm and 2mm shaft rod tests, and Examples 3-4 have slight reticulation under the 3mm shaft rod test. Examples 1-2 still remain free of reticulation and cracks under the 1-3mm shaft rod test, and both have good flexibility, indicating that the combined effect of nano hydroxyapatite and vinyl trimethoxy silane is better, and the zeolite powder of Example 1 will not affect the flexibility performance. The high specific surface area and surface energy of nano-hydroxyapatite prompt it to form an orderly arranged nanostructure in the polymer matrix, which, as a bridge for stress transmission, can provide additional deformation capacity when bent or stretched, effectively disperse and absorb external forces, thereby helping to improve the flexibility and overall mechanical properties of the latex material. The vinyl functional group in vinyl trimethoxy silane participates in the cross-linking reaction of the polymer to enhance the connection between the molecular chains, thereby improving the strength and toughness of the material. Vinyl trimethoxy silane is added to the modification of Example 2, and its flexible siloxane segment is introduced into the polymer molecule, which increases the flexibility of the material. At the same time, due to the steric hindrance effect and large atomic radius of silicon atoms, the silicon segment migrates to the surface during the formation of the latex film, which not only improves the softness of the mask, but also increases the surface smoothness, reduces the dynamic and static friction coefficients, and finally plays a positive effect on the improvement of flexibility, making the latex mask softer and more comfortable. In contrast, although comparative examples 1-2 also use organosilicon compounds, vinyl trimethoxysilane, γ-aminopropyl triethoxysilane, and N-(β-aminoethyl)-γ-aminopropyl methyl dimethoxysilane have different chemical structures and cannot have the same effect, and the improvement in flexibility is slightly inferior. Comparative example 3 simply mixes highly flexible natural latex with low-flexibility water-based polyurethane as the raw material for the latex mask. It can still maintain the performance under the 1mm shaft test, but slight reticulation appears under the 2mm and 3mm shaft tests. The flexibility is the lowest, which does not help to improve the comfort and durability of the mask.
[0051] Test Example 3 Durability Testing Latex generally refers to a colloidal emulsion formed by polymer particles dispersed in water. Test Example 3 The latex masks prepared in Examples 1-4 and Comparative Example 3 were subjected to durability tests, including tensile strength and elongation at break. The tests were conducted in accordance with the national standard GB / T 10654-2001 "Determination of tensile strength and elongation at break of porous polymer elastic materials". The test data were averaged and summarized in Table 3. .
[0052] In the durability test, tensile strength and elongation at break are used as measurement indicators for testing. Tensile strength refers to the maximum pressure that a material can withstand during the stretching process, and elongation at break indicates the maximum extent to which a material can stretch before breaking. In Examples 1-3, the addition of nano-hydroxyapatite improves the tensile strength and elongation at break compared to Example 4 and Comparative Example 3. The addition of nano-hydroxyapatite can reduce the friction coefficient of the material and improve wear resistance. Its high specific surface area enhances the interface bonding with the polyurethane matrix, effectively disperses stress, increases the toughness and elasticity of the material, and thus improves the overall mechanical properties of the material. The difference between Example 3 and Example 1-2 is that only nano-hydroxyapatite is added without adding vinyltrimethoxysilane, while the difference between Example 1 and Example 2 is that zeolite powder is added for compounding, and its pore structure provides more deformation space for the material and improves the distribution of internal stress of the material, which enables it to withstand greater stress without breaking during the stretching process, thereby improving the tensile strength and the growth rate at break. Compared with Comparative Example 3, Example 4 adds vinyl trimethoxysilane to modify the waterborne polyurethane. The flexible silicon oxygen bond provides better elasticity and fatigue resistance, and reduces friction and improves wear resistance, so that the latex mask can still maintain its performance after repeated use and stretching, and is not easy to break or damage, which plays a positive role in improving the durability of the latex mask. Highly durable latex masks can maintain their shape and function during long-term use, reduce damage and scrapping caused by wear or tear, and increase the number of uses.
[0053] The preferred specific embodiments of the present invention are described in detail above. It should be understood that a person skilled in the art can make many modifications and changes based on the concept of the present invention without creative work. Therefore, any technical solution that can be obtained by a person skilled in the art through logical analysis, reasoning or limited experiments based on the concept of the present invention on the basis of the prior art should be within the scope of protection determined by the claims.
Claims
1. A method for preparing a latex mask, characterized in that: The method comprises the following steps, in parts by weight: (1) Add 10-15 parts of 1,5-pentanediol and 0.5-1 parts of sodium 5-sulfoisophthalate to 250-350 parts of water, stir at 160-180°C for 1-2 hours, cool to 70-90°C, add 0.05-0.15 parts of dibutyltin dilaurate and 10-15 parts of glutaric acid, stir at 130-150°C for 1-2 hours, concentrate and dry to obtain sulfonate diol; (2) 8-10 parts of isophorone diisocyanate, 8-10 parts of polytetramethylene glycol, and 0.1-0.2 parts of trimethylolpropane are mixed, and 0.5-1.5 parts of emulsifier, 0.1-0.2 parts of nano-hydroxyapatite, and 0.4-0.6 parts of silane modifier are added, and ultrasonic dispersion is performed for 10-30 minutes to obtain a waterborne polyurethane prepolymer; 0.02-0.08 parts of catalyst and 2-3 parts of sulfonate diol are added, and the mixture is stirred at 70-80°C for 3-5 hours, and then the temperature is lowered to 60-70°C and 10-20 parts of Acetone is added to reduce the viscosity, 0.5-1 parts of chain extender and 0.2-0.4 parts of 1,4-butanediol are added, stirring is continued for 1-2 hours, cooled to 30-40°C, 0.2-0.6 parts of triethylamine are added for neutralization reaction and stirring is continued for 0.5-1 hour, added to 40-50 parts of water and stirred at a speed of 1000-1500r / min for 0.5-1 hour, and finally 0.1-0.3 parts of ethylenediamine are added and stirred at room temperature for 1-1.5 hours for further chain extension, and acetone is removed by concentration at 50°C to obtain the modified waterborne polyurethane emulsion; (3) adding 20-30 parts of zeolite powder to 140-200 parts of water, and ultrasonically dispersing for 10-30 minutes to obtain a zeolite powder dispersion, adding the modified aqueous polyurethane emulsion obtained in step (2) to the zeolite powder dispersion, and stirring at room temperature for 1-1.5 hours to obtain a composite modified aqueous polyurethane emulsion; (4) 30-40 parts of natural latex, 50-60 parts of composite modified waterborne polyurethane emulsion, 0.5-1 part of defoamer, 0.5-1 part of thickener and 0.4-0.6 part of wetting agent are mixed, and mixed in a high-speed disperser at 1500-2000 r / min for 0.5-1 hour to obtain a mixed emulsion, and the mask mold is directly immersed in the mixed emulsion for 2-4 times, dried at 80-100° C., and demolded after molding to obtain the latex mask.
2. The method for preparing a latex mask as claimed in claim 1, characterized in that: In the step (2), the particle size of the nano-hydroxyapatite is 100-300 nm.
3. The method for preparing a latex mask according to claim 1, characterized in that: The silane modifier in step (2) is vinyltrimethoxysilane.
4. The method for preparing a latex mask according to claim 1, characterized in that: The emulsifier in step (2) is dodecylphenol polyoxyethylene ether OP-10.
5. The method for preparing a latex mask according to claim 1, characterized in that: In the step (2), the chain extender is any one of 2,2-dihydroxymethylpropionic acid, 1,2-propylene glycol, diethylene glycol, 2-methylpentanediamine, and 1,6-hexanediamine.
6. The method for preparing a latex mask according to claim 1, characterized in that: The thickener in step (4) is hydroxyethyl cellulose.
7. The method for preparing a latex mask according to claim 1, characterized in that: The immersion thickness in the step (4) is 0.2-0.4 cm.
8. A latex mask, characterized in that: Prepared by the method according to any one of claims 1 to 7.
Citation Information
Patent Citations
Cool breathable latex product and preparation method thereof
CN113549243A